PENGEMBANGAN KOLEKSI DEPOSIT DI DINAS PERPUSTAKAAN DAN KEARSIPAN KALIMANTAN BARAT - Nor Mukhlishin; Totok Priyadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRACTThe purpose of this study was to determine the planning of Collection Development and the layout of the public library of the Deposit Service of the Library and Archives of West Kalimantan. This research used qualitative research, the source of the research was from the Head of the Deposit Library, the Library technician section. Data collection methods are observation, analysis, research, interviews, documentation. The analysis shows that the West Kalimantan Library and Archives Service Deposit Collection Room is part of the Central Library of the Republic of Indonesia West kalimantan Library and Archives Service which makes a function for archiving from the Deposit Library Section, the deposit room where published works are stored and recorded works are increasingly increasing every year, as for the functions associated with the Library Room, namely, making a builder library, reference library, deposit library, research library and preservation library, and population from the capital city of West Kalimantan Province. The Deposit Room comes from a local publisher in West Kalimantan, especially after the issuance of the RI Law No. 4 of 1990 concerning the handover of the saving of printed and recorded works as amended by Law No. 13 year 2018.Keywords :Collection Development, deposit collection